Design of Wireless Disaster Alarm System Using Microwave Links - Gustilo, Reggie C. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Two microwave links operating at 5GHz and 26GHz are characterized in this research to correlate the rain rate in terms of power attenuations in the links. Regression analysis is used to estimate the degradation in the received power levels in the microwave links in terms of the measured rain rates from traditional tipping buckets. The regression model is compared to the regression analysis models done in different countries. Results show that the estimation done in this research is more appropriate to be used in the Philippines compared to the existing models. This research is the basis of all the highly scalable wireless sensors systems that aim to determine the classification of tropical rains according to the received power levels in the microwave links. Finally, a knee point of -85dBm in the received signal level was observed in the 26GHz band that serves as the transition point between the safe condition yielding 0dB loss and unsafe rain conditions that increase the packet loss rates of the received signals. This knee point may serve as a trigger point for disaster alarm systems